The Begonia of Veracruz: Additions and revisions - McMillan, Patrick D.; Wyatt, Graham; Morris, Rekha (Instituto de Ecología, A.C., 2006)
Field explorations and examination of herbarium specimens were utilized to document the diversity of Begonia species found within the state of Veracruz. Thirty species were found to be of native occurrence in the state. One species, Begonia involucrata is reported as new to Mexico and is disjunct from the nearest documented populations in Costa Rica. Begonia sericoneura is added as new to the state of Veracruz. Examinations of new material, live specimens and re-examination of previously collected material were utilized to revise descriptions of Begonia carolineifolia, B. involucrata, B. lyniceorum, B. sericoneura and B. sousae. Stomatal arrangements were determined for 28 of the 30 taxa. Solitary stomatal arrangements in section Gireoudia are shown to be more common than previous reports would indicate with 7 of the 18 species examined not exhibiting stomatal clusters. A key to the native taxa of the state of Veracruz is presented. Habitat, elevational and distributional patterns are also reported and discussed.